A Facile One‐Step Approach for Constructing Multidimensional Ordered Nanowire Micropatterns via Fibrous Elastocapillary Coalescence. Issue 18 (18th March 2019) - Bian, Ruixin; Meng, Lili; Guo, Cheng; Tang, Zhongxue; Liu, Huan
Abstract: Nanowire (NW) based micropatterns have attracted research interests for their applications in electric microdevices. Particularly, aligning NWs represents an important process due to the as‐generated integrated physicochemical advantages. Here, a facile and general strategy is developed to align NWs using fibrous elastocapillary coalescence of carbon nanotube arrays (ACNTs), which enables constructing multidimensional ordered NW micropatterns in one step without any external energy input. It is proposed that the liquid film of NW solution is capable of shrinking unidirectionally on the top of ACNTs, driven by the dewetting‐induced elastocapillary coalescence of the ACNTs. Consequently, the randomly distributed NWs individually rotate and move into dense alignment. Meanwhile, the aggregating and bundling of ACNTs is helpful to produce carbon nanotube (CNT) yarns connecting neighboring bundles. Thus, a micropatterned NW network composed of a top‐layer of horizontally aligned NWs and an under‐layer of vertical ACNT bundles connected by CNT yarns is prepared, showing excellent performance in sensing external pressure with a sensitivity of 0.32 kPa −1 . Moreover, the aligned NWs can be transferred onto various substrates for constructing electronic circuits. The strategy is applicable for aligning various NWs of Ag, ZnO, Al2 O3, and even living microbes. The result may offer new inspiration for fabricating NW‐based functional micropatterns. Abstract : Fibrous elastocapillary coalescence is used to align various nanowires without external energy input, by which multidimensional ordered micropatterns with multiple functions are prepared. The approach provides a new option to design functional micropatterns for force sensing, flexible electrodes, and complex circuits.